Altered Default Mode Network on Resting-State fMRI in Children with Infantile Spasms - Wang, Ya; Li, Yongxin; Wang, Huirong; Chen, Yanjun; Huang, Wenhua (Frontiers in Neurology, 2017)
Abstract: Infantile spasms (IS) syndrome is an age-dependent epileptic encephalopathy which occurs in children characterized by spasms, impaired consciousness and hypsarrhythmia. Abnormalities in default mode network (DMN) might contribute to the loss of consciousness during seizures and cognitive deficits in children with IS. The purpose of the present study was to investigate the changes in DMN with functional connectivity and amplitude of low-frequency fluctuation (ALFF) the two methods to discover the potential neuronal underpinnings of infantile spasms. The consistency of the two calculate methods of DMN abnormalities in IS patients was also our main focus. To avoid the disturbance of interictal epileptic discharge, our testing was performed within the interictal durations without epileptic discharges. Resting state fMRI data were collected from 13 patients with IS and 35 sex- and age-matched healthy controls. Functional connectivity analysis with seed in posterior cingulate cortex (PCC) was used to compare the differences between two groups. We chose PCC as the seed region because PCC is the only node in the DMN that directly interacts with virtually all other nodes according to previous studies. Furthermore, the ALFF values within the DMN were also calculated and compared between the two groups. The functional connectivity results showed that IS patients exhibited markedly reduced connectivity between posterior seed region and other areas within DMN. In addition, part of the brain areas within the DMN showing significant difference of functional connectivity had significantly lower ALFF signal in the patient group than that in the healthy controls. The observed disruption in DMN through the two methods showed that the the coherence of brain signal fluctuation in DMN during rest were broken in IS children. Neuronal functional impairment or altered integration in DMN would be one neuroimaging characteristic, which might help us to understand the underlying neural mechanism of IS. Further studies are needed to determine whether the disturbed functional connectivity and ALFF observed in the DMN are related to cognitive performance in IS patients.